ANALISIS PERBANDINGAN ALTERNATIF PERKUATAN STABILITAS LERENG PADA REST AREA JALAN TOL SEMARANG – SOLO (Studi Kasus Rest Area Km. 456) - Angga Wisnu Murti; Henny Pratiwi Adi; M. Faiqun Niam (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2023)
Soil/slope stabilization is a method used to increase the bearing capacity of a soil layer by giving special treatment to the soil layer. This study aims to determine the criteria for selecting the type of reinforcement, the advantages and disadvantages of geotextile woven reinforcement, gabions and geoframes, as well as to determine the priority order of slope reinforcement based on existing criteria in the construction work of the Semarang - Solo km toll road rest area. 456. The data in the study were obtained through a questionnaire with the respondents of this study consisting of 10 people who came from the job owner, job executor and work supervisory consultant. To choose slope stability reinforcement there are 5 criteria, namely cost, implementation time, labor, availability of materials and functions. The type of reinforcement used there are 3 alternatives including woven geotextiles, gabions and geoframes. Data analysis using AHP (Analitycal Hierarchy Process) method, data processing using Expert Choice software. The results of this study indicate that the woven geotextile reinforcement function criteria are superior with a weight of 0.375. Then from the criteria for the implementation of superior woven geotextile reinforcement with a weight of 0.587. Woven geotextiles are also superior in terms of labor and material availability with weights of 0.510 and 0.586, respectively. Meanwhile, in the criteria of superior gabion reinforcement function with a weight of 0.456. Woven geotextile reinforcement is the first priority based on the above criteria with a weight of 0.41,the priority of selecting the second reinforcement using gabions with a weight of 0.341 and strengthening using a geoframe is on the third priority with a weight of 0.248. While the realization in the field the use of woven geotextiles and geoframes is the most widely used compared to using gabions.